2023
DOI: 10.3389/fneur.2022.1078147
|View full text |Cite
|
Sign up to set email alerts
|

Application of TBSS-based machine learning models in the diagnosis of pediatric autism

Abstract: ObjectiveTo explore the microstructural changes of white matter in children with pediatric autism by using diffusion kurtosis imaging (DKI), and evaluate whether the combination of tract-based spatial statistics (TBSS) and back-propagation neural network (BPNN)/support vector machine (SVM)/logistic regression (LR) was feasible for the classification of pediatric autism.MethodsDKI data were retrospectively collected from 32 children with autism and 27 healthy controls (HCs). Kurtosis fractional anisotropy (FAK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…2022 ) in ASD compared with HC. Lower DKI metrics have been interpreted as developmental abnormalities, axon damage ( He et al. 2022 ), differences in the microstructural environment such as decreased neuronal density ( Irie et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2022 ) in ASD compared with HC. Lower DKI metrics have been interpreted as developmental abnormalities, axon damage ( He et al. 2022 ), differences in the microstructural environment such as decreased neuronal density ( Irie et al.…”
Section: Discussionmentioning
confidence: 99%
“…The variability noted across studies is likely also due to the genetic and observed phenotypic diversity among diagnosed individuals and the differing ages of study participants ( Sydnor and Aldinger 2022 ). Our sample is composed of a relatively older (33.5 ± 8.8 years) and wider (19 to 52 years) range of ages than previous DKI reports, including on pediatric ( He et al. 2022 ; Tang et al.…”
Section: Discussionmentioning
confidence: 99%